2020
DOI: 10.3390/pathogens9010070
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pathogenic and Nonpathogenic Fusarium oxysporum Isolates Associated with Commercial Tomato Crops in the Andean Region of Colombia

Abstract: In Colombia, tomato production under protected conditions represents an important economic contribution to the agricultural sector. Fusarium wilt diseases, caused by pathogenic formae speciales of the soil-borne fungus Fusarium oxysporum Schltdl., cause significant yield losses in tomatoes throughout the world. Investigation of the F. oxysporum–tomato pathosystem in Colombia is required to develop appropriate alternative disease management. In this study, 120 fungal isolates were obtained from four different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 50 publications
0
22
0
2
Order By: Relevance
“…The Fol59 strain isolated from tomato plants and identified as F. oxysporum f. sp. lycopersici (Fol) Race 2 (Carmona et al, 2020) was used in all the assays. Fol59 was mantained on PDA (Potato Dextrose Agar) culture medium added with fresh tomato tissue extract (6 g.L -1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Fol59 strain isolated from tomato plants and identified as F. oxysporum f. sp. lycopersici (Fol) Race 2 (Carmona et al, 2020) was used in all the assays. Fol59 was mantained on PDA (Potato Dextrose Agar) culture medium added with fresh tomato tissue extract (6 g.L -1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Plant pathogenic fusaria have been assessed for interspecific genetic variation to identify genomic features important for plant host infection [ 1 , 2 ]. In addition, intraspecific genetic variation is a powerful tool to identify potential mechanisms for disease development by pathogenic fungi [ 31 , 32 ]. This study presents a whole genome comparison between two F. oxysporum isolates collected from koa roots, one pathogenic ( Fo koae 44) and one non-pathogenic ( Fo 170) isolates.…”
Section: Discussionmentioning
confidence: 99%
“…However, Fusarium wilt of tomato is one of the most important diseases, which affect all plant stages (seedling stage, flowering stage, and fruiting stage). Also, it can affect the whole plant parts, leaves and stems [9, 12,13,17,[19][20][21][22][23][24]. Agrios [25] reported that the disease is most destructive in warm climates and warm sandy soil of temperate regions.…”
Section: Tomato Plant: Botanical Notesmentioning
confidence: 99%
“…Fusarium wilt around the world is considered as one of the most important diseases of tomato [17][18][19]21,22,24,[26][27][28][29]. The causal agent of this disease is Fusarium oxysporum lycopersici [12,19,20,24,[29][30][31][32].…”
Section: Tomato Plant: Botanical Notesmentioning
confidence: 99%
See 1 more Smart Citation